Integrasi keterampilan abad 21 (4C) dalam pembelajaran PAI: Strategi guru dalam membangun karakter adaptif dan religius - Mubarokah, Syifa Fatihatul; Hermawan, Wawan; Budiyanti, Nurti (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2026)
Moral degradation and ethical erosion in the digital era necessitate a realignment between technical competence and spiritual maturity in education. This study aims to analyze strategies for integrating 21st-century skills (the 4Cs: Critical Thinking, Creativity, Collaboration, and Communication) into Islamic Religious Education (PAI) to foster student character that is adaptive yet deeply religious. Employing a descriptive qualitative design with a case study approach, this research involved three PAI teachers at a State Junior High School in Bandung. Data were collected through in-depth interviews and document analysis of Deep Learning-based teaching modules, then analyzed using thematic and content analysis techniques. The findings reveal the phenomenon of "Competence Islamization" as a primary pedagogical strategy. Specifically, Critical Thinking is internalized as the capacity for Tabayyun (verification) to filter hoaxes; Creativity is realized through the utilization of AI for digital Syiar (propagation); Collaboration functions as a mechanism of Ta'awun (mutual assistance) in Quranic literacy; and Communication is framed by the principle of Qaulan Ma'rufan(honorable speech) to maintain digital etiquette. This study concludes that PAI serves not merely to transfer religious knowledge but acts as an ethical foundation that frames students' global competencies. The implications of this study offer a practical model for educators to bridge the gap between digital literacy and moral integrity through meaningful and reflective learning approaches. Abstrak Degradasi moral dan erosi etika di era digital menuntut penyelarasan kembali antara kompetensi teknis dan kematangan spiritual dalam pendidikan. Studi ini bertujuan untuk menganalisis strategi integrasi keterampilan abad ke-21 (4C) Critical Thinking, Creativity, Collaboration, Communication ke dalam pembelajaran Pendidikan Agama Islam (PAI) guna membentuk karakter siswa yang adaptif namun tetap religius. Menggunakan desain kualitatif deskriptif dengan pendekatan studi kasus, penelitian ini melibatkan tiga guru PAI di salah satu SMP Negeri di Kota Bandung. Data dikumpulkan melalui wawancara mendalam dan analisis dokumen Modul Ajar berbasis Deep Learning, kemudian dianalisis menggunakan teknik analisis tematik dan isi. Hasil penelitian mengungkapkan fenomena "Islamisasi Kompetensi" sebagai strategi pedagogis utama. Temuan menunjukkan bahwa Critical Thinking diinternalisasi sebagai kemampuan Tabayyun untuk memfilter hoaks; Creativity diwujudkan melalui pemanfaatan AI untuk Syiar digital; Collaboration difungsikan sebagai mekanisme Ta'awun (tolong-menolong) dalam literasi Al-Qur'an; dan Communication dibingkai oleh prinsip Qaulan Ma'rufan untuk menjaga adab digital. Penelitian ini menyimpulkan bahwa PAI tidak hanya berperan mentransfer pengetahuan agama, tetapi bertindak sebagai fondasi etis yang membingkai kompetensi global siswa. Implikasi studi ini menawarkan model praktis bagi pendidik dalam menjembatani kesenjangan antara literasi digital dan integritas akhlak melalui pendekatan pembelajaran yang bermakna dan reflektif.